A software tool and strategy for peptidoglycomics, the high-resolution analysis of bacterial peptidoglycans via LC-MS/MS - Marcel G. Alamán-Zárate; Brooks J. Rady; Raphael Ledermann; Neil Shephard; Caroline A. Evans; Mark J. Dickman; Robert D. Turner; Aline Rifflet; Ankur V. Patel; Ivo Gomperts Boneca; Philip S. Poole; Marshall Bern; et al. (Communications Chemistry)
Abstract Peptidoglycan is an essential component of the bacterial cell envelope—a mesh-like macromolecule that protects the bacterium from osmotic stress and its internal turgor pressure. The composition and architecture of peptidoglycan is heterogeneous and changes as bacteria grow, divide, and respond to their environment. Though peptidoglycan has long been studied via LC-MS/MS, the analysis of this data remains challenging as peptidoglycan’s unusual composition and branching can’t be handled by proteomics software. Here we describe user-friendly open-source tools and a web interface for building peptidoglycan databases, performing MS searches, and predicting the MS/MS fragmentation of muropeptides. We then use Rhizobium leguminosarum to describe a step-by-step strategy for the high-resolution analysis of peptidoglycan. The unprecedented detail of R. leguminosarum’s peptidoglycan composition (>250 muropeptides) reveals even the subtlest remodelling between growth conditions. These new and easier to use tools enable more systematic analyses of peptidoglycan dynamics.